GENDER DIVERSITY ON BOARD AND ITS RELEVANCE TO FIRM PERFORMANCE: A STUDY ON PHARMACEUTICAL INDUSTRY OF BANGLADESH - Fahad, Hossain Ahmmed; Mahmud, Imran; Rahman, Atkia Nabiha (Asian Finance & Banking Review, 2022)
The study tries to examine the relationship between gender diversity on the Board and firms’ profitability in Bangladesh’s Pharmaceutical industry. The study employs a panel data approach with all the Pharmaceutical companies listed under Dhaka Stock Exchanges. The sample period covers eight years from 2012-2019. To conduct the study, Return on Equity and Tobin’s Q was taken as a proxy of accounting measure of profitability and market measure of profitability, respectively. The proportion of women on board structure was taken as a proxy for gender diversity. Some other variables: board size, firm age, leverage, and firm size, were incorporated to control the effect of these variables on profitability. The study reveals that gender diversity shows a positive but insignificant relationship with the firm’s performance in terms of ROE. The R square of this model was 11.67%. In terms of Tobin’s Q, gender diversity exhibited a significant positive relationship with firm performance. The R square of this model was 17%. This implies that the market ascribes a great value to the inclusion of women in board structure since it increases the board structure’s independence and profitability. JEL Classification Codes: C12, F65, L25.